Incautación de productos con observaciones sanitarias, por la UFREMID, Región La Libertad, enero- junio 2016 - Palco Cotrina, Alicia (2018)
This report on pre-professional practices aimed to identify the characteristics of the products with health observations in the La Libertad Region, January - June 2016, which were seized by the Functional Unit for the Regulation of Drugs, Supplies and Drugs (UFREMID). The study was carried out using the technique of structured observation, graphs were constructed for the results, and it was found that the pharmacies were the establishments where most products were seized with sanitary observations and the majority in the district of Trujillo. According to its classification, pharmaceutical products comprised 54.74% of all the products seized. The 96.63% of the seized products had the sanitary observation of expired expiration date, 1.69% of without sanitary registration. Among the medications seized were analgesics, antibiotics, corticosteroids, antihypertensive drugs, but it was the anti-inflammatory drugs that were found with a higher percentage of 31.83%. On the other hand, the drugs that were found most falsified were: Apronax 550mg, Panadol anti-flu, Bactrim F 800 / 160mg and GRAVOL Dimenhydrinate 50 mg